Non-muslims in mosques : expected etiquettes and participation with the underlying reasons - Nangkula, Utaberta; Ismail, Nor Atiah; Mohd Ariffin, Noor Fazamimah; Ismail, Sumarni; Mohd Yunus, Mohd Yazid; Yap, Heng Hee (American-Eurasian Network for Scientific Information (AENSI), 2015)
As the economy rises dramatically, cities are becoming increasingly crowded places with multicultural and multi-religious dwellers. Mosques, with their unique culture and architecture, thus become significant places that attract concern and interest from non Muslims community. However, the etiquette for non-Muslims in mosques are often interpreted differently when we look at the rules in the mosques across the world. The impacts of different understanding among multicultural communities about non-Muslims in mosques should not be underestimated when Islam nowadays are being treated with much misunderstanding. In order to generate mutual agreement, especially among non Muslims and Muslims, this essay, discuss on the extent a non-Muslim can involve in Mosque activities in different societies and its reasons by analyzing the visiting etiquette required for selective mosques, each with its particular cultural background.